Comparative Analysis of Polyphenolic Acids from Various Zea mays Parts in Ultrasound-Assisted Extraction - David Řepka; Lubomír Lapčík (Foods)
In this study, we compared different parameters in the ultrasound-assisted extraction of polyphenolic acids from seven parts of Zea mays (kernels, leaves, stems, corn silks, roots, the whole plant, and the whole fermented plant) to identify its richest natural sources. Additionally, the correlation between extraction parameters and polyphenol yield was investigated. The extraction was performed using ultrasound at varying powers (480 or 240 W) and frequencies (80 or 37 kHz). Total phenolic content (TPC) was determined using the Folin–Ciocalteu assay, while radical scavenging activity (RSA) was assessed via the DPPH assay. The TPC values ranged from 0.69 ± 0.00008 mg GAE/g to 4.07 ± 0.0004 mg GAE/g in corn. RSA analysis revealed the highest scavenging activity in corn silk (80.06% ± 1.01) and the lowest in kernels (2.77% ± 0.90). High-performance liquid chromatography identified up to 22 different phenolic acids per sample, with the 5 most abundant being chlorogenic acid, protocatechuic acid ethyl ester, quercetin, sinapic acid, and trans-cinnamic acid. The study found small effects of power and frequency on the extraction efficiency. This suggests a practical advantage for industrial-scale applications, as using 240 W instead of 480 W under the same conditions can reduce energy consumption without compromising yield.